Lanthanide Ion Resonance‐Driven Rayleigh Scattering of Nanoparticles for Dual‐Modality Interferometric Scattering Microscopy. Issue 32 (17th August 2022) - Ding, Lei; Shan, Xuchen; Wang, Dejiang; Liu, Baolei; Du, Ziqing; Di, Xiangjun; Chen, Chaohao; Maddahfar, Mahnaz; Zhang, Ling; Shi, Yuzhi; Reece, Peter; Halkon, Benjamin; et al.
Abstract: Light scattering from nanoparticles is significant in nanoscale imaging, photon confinement. and biosensing. However, engineering the scattering spectrum, traditionally by modifying the geometric feature of particles, requires synthesis and fabrication with nanometre accuracy. Here it is reported that doping lanthanide ions can engineer the scattering properties of low‐refractive‐index nanoparticles. When the excitation wavelength matches the ion resonance frequency of lanthanide ions, the polarizability and the resulted scattering cross‐section of nanoparticles are dramatically enhanced. It is demonstrated that these purposely engineered nanoparticles can be used for interferometric scattering (iSCAT) microscopy. Conceptually, a dual‐modality iSCAT microscopy is further developed to identify different nanoparticle types in living HeLa cells. The work provides insight into engineering the scattering features by doping elements in nanomaterials, further inspiring exploration of the geometry‐independent scattering modulation strategy. Abstract : Benefitting from the enhanced resonance of lanthanide ions, the geometry dependence of Rayleigh scattering engineering is broken through by adjusting the ion types in nanoparticles, which results in an efficient and dual‐modality nanoprobe for scattering‐based microscopy.